2013
DOI: 10.1371/journal.pone.0062787
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Reducing Sexual and Reproductive Risk Behaviors Based on the Information-Motivation-Behavioral Skills (IMB) Model among Unmarried Rural-To-Urban Female Migrants in Shanghai, China

Abstract: BackgroundDue to the increase of premarital sex and the lack of reproductive health services, unmarried rural-to-urban female migrants experience more risks of sex and reproductive health (SRH). This study was designed to describe SRH related knowledge, attitude and risk behaviors among unmarried rural-to-urban female migrants and examine the predictors of reducing sexual and reproductive risk behaviors based on information-motivation-behavioral skills (IMB) model and to describe the relationships between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 26 publications
4
19
2
Order By: Relevance
“…Our results suggest motivation had a direct effect on behavioral skills, but also had a direct effect on sexual risk behavior. This partial mediation effect of motivation on sexual risk behavior through behavioral skills is consistent with other IMB model research [21,25,2729,31,35,44,54], but conflicts with evidence of a fully-mediating effect [32,36,43,49]. Thus, motivation and behavioral skills remain important components of the IMB model, but some populations may rely more heavily upon behavioral skills to enact protective behavior compared to others.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results suggest motivation had a direct effect on behavioral skills, but also had a direct effect on sexual risk behavior. This partial mediation effect of motivation on sexual risk behavior through behavioral skills is consistent with other IMB model research [21,25,2729,31,35,44,54], but conflicts with evidence of a fully-mediating effect [32,36,43,49]. Thus, motivation and behavioral skills remain important components of the IMB model, but some populations may rely more heavily upon behavioral skills to enact protective behavior compared to others.…”
Section: Discussionsupporting
confidence: 85%
“…Specifically, past studies found that information does not always have a direct effect on sexual risk behavior, but many studies suggest that information remains a necessary component of HIV prevention interventions because of the influence knowledge has on behavioral skills. Our results fit with other studies that found that information significantly predicted behavioral skills, but did not directly predict sexual risk behavior [21–22,24,32,44,4849,54]; however, our results conflict with those that found no effect of information [2528,31,35] and those with a direct relationship with condom use [22,43]. It has been argued that the importance of HIV prevention information may be attenuated within populations with higher levels of knowledge [37], and we found low levels of HIV prevention knowledge within this sample of alcohol-using STI clinic patients providing additional evidence in support of this hypothesis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…All the questions were constructed from answers on a 5-point Likert scale (1 completely agree to 5 completely disagree) [33]. Four items (e.g., What do you think of married women who have sexual intercourse with males besides their husbands?)…”
Section: Methodsmentioning
confidence: 99%
“…1) It combines the concepts of other theories, such as the self-efficacy concept from the social cognitive theory model and the theory of reasoned action by enhancing the understanding the motivation. The model also considers various types of factors, such as socio-psychological factors that may affect the human behavior [19] ; 2) as an integrated multivariable model, it has been proved effective in some people groups, such as high school students [20] , unmarried rural-to-urban female migrants [21] ; 3) the model can translate theory into practice more easily; and 4) the IMB model are regarded as highly generalizable for HIV risk behavior prevention among various at risk populations [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%